Synthesis and steroid sulfatase inhibitory activities of N-phosphorylated 3-(4-aminophenyl)-coumarin-7-O-sulfamates12. Issue 6 (22nd April 2016) - Daśko, Mateusz; Masłyk, Maciej; Kubiński, Konrad; Aszyk, Justyna; Rachon, Janusz; Demkowicz, Sebastian
Abstract : In the present work, we report convenient methods for the synthesis and biological evaluation of N -phosphorylated derivatives of 3-(4-aminophenyl)-coumarin-7- O -sulfamate as potential steroid sulfatase (STS) inhibitors. Abstract : In the present work, we report convenient methods for the synthesis and biological evaluation of N -phosphorylated derivatives of 3-(4-aminophenyl)-coumarin-7- O -sulfamate as potential steroid sulfatase (STS) inhibitors. Their binding modes were modeled using docking techniques. The inhibitory effects of the synthesized compounds were tested on STS isolated from human placenta. All of the newly synthesised coumarin derivatives were powerful inhibitors of STS with IC50 values ranging between 0.19 and 0.78 μM. In particular, we found that 3-[4-(diphenoxy-phosphorylamino)-phenyl]-coumarin-7- O -sulfamate10e and 3-[4-(dibenzyloxy-phosphorylamino)-phenyl]-coumarin-7- O -sulfamate10f produced the highest inhibitory effects, with IC50 values of 0.19 and 0.24 μM, respectively (IC50 values of 1.38 μM for coumarin-7- O -sulfamate2 and 1.03 μM for coumate3 used as reference). The structure–activity relationships of the synthesized coumarin derivatives toward the STS enzyme were discussed.